Infographics as a Learning Tool in Higher Education: The Design Process and Perception of an Instructional Designer - Alyahya, Dalia M. (International Journal of Learning, Teaching and Educational Research, 2019)
Infographics, as an instructional tool, enable support in the creation of an easy to read platform for learners. Steps involved to develop an infographic, play an essential role in optimizing visual literacy transfers. This study has presented a qualitative analysis of the proposed design strategy, which focuses on the infographic development process. The results have proposed that Infographics assignment design when included in instructional technology disciplines, helps instructional designers to enhance message delivery during visual transfers that eventually leads to increased learning interests among learners. The study also revealed five vital themes that emerged upon analyzing the collected data from participants involved. The present study has provided research scholars, an insight of the developed state-of-the-art tool, which in future research studies might serve as a basis for the development of an Instructional Infographic model. https://doi.org/10.26803/ijlter.18.1.1